Kandungan Logam Berat Timbal (Pb) pada Ikan di Sungai Lamat Kabupaten Magelang - Arkianti, Nisa; Dewi, Nur Kusuma; Tri Martuti, Nana Kariada (Universitas Negeri Semarang, 2019)
Lead (Pb) is a heavy metal that is toxic to humans found in nature, including in the waters of the Lamat River. Fish is one bioindicator of the level of heavy metal pollution that occurs in the waters. This study aims (1) to determine the concentration of Pb in water in the Lamat River and (2) to determine the accumulation of Pb heavy metals in fish on the Lamat River in Magelang Regency. This study is an observational analytic study with a qualitative approach. The sampling technique is purposive sampling. The environmental parameters measured are temperature, pH, DO, BOD, COD, and current. The lead content (Pb) in water and fish was measured using Atomic Absorption Spectrophotometry (AAS). The results showed that temperature, pH, DO, BOD, COD, and currents were still within the proper range for fish life. The level of heavy metal lead (Pb) contained in the water at the three stations was not detected. While the Pb content in fish on the River between 0.3807-0.7268 µg/g. Conclusion; water in Sungai Lamat does not exceed the SNI quality standard of 0, 01 mg/L, while the Pb concentration in fish in Sungai Lamat has exceeded the SNI quality standard, which is 0.3 µg/g. That way, it is not recommended to consume fish that are on the Lamat River. Timbal (Pb) merupakan logam berat yang bersifat toksik bagi manusia yang terdapat di alam, termasuk di perairan Sungai Lamat. Ikan merupakan satu satu bioindikator tingkat pencemaran logam berat yang terjadi di dalam perairan. Penelitian ini bertujuan (1) mengetahui konsentrasi Pb pada air di Sungai Lamat dan (2) mengetahui akumulasi logam berat Pb pada ikan di Sungai Lamat Kabupaten Magelang. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan kualitatif. Teknik pengambilan sampel dengan purposive sampling. Parameter lingkungan yang diukur adalah suhu, pH, DO, BOD, COD dan arus. Kandungan timbal (Pb) pada air dan ikan diukur menggunakan Atomyc Absorption Spectrophotometry (AAS). Hasil penelitian menunjukkan bahwa suhu, pH, DO, BOD, COD dan arus masih berada dalam kisaran yang layak bagi kehidupan ikan. Kadar logam berat timbal (Pb) yang terkandung dalam air pada ketiga stasiun tidak terdeteksi alat. Sedangkan kandungan Pb pada ikan di Sungai antara 0,3807-0,7268 µg/g. Kesimpulan; air di Sungai Lamat tidak melebihi baku mutu SNI yang sebesar 0, 01 mg/L, sedangkan konsentrasi Pb pada ikan di Sungai Lamat telah melebihi baku mutu SNI yaitu 0,3 µg/g. Dengan begitu, tidak dianjurkan untuk mengkonsumsi ikan yang berada di Sungai Lamat.